Brain Developmental Differences Between Preterm-born Twins and Singletons: A Multi-modal MRI Study - Tingting Liu; Hongxi Zhang; Yuqing You; Weihao Zheng; Zhiyong Zhao; Tianmei Liu; Xiaoli Su; Fengyu Tian; Yi Zhang; Dan Wu (Galenos Yayinevi, 2021)
Aim:Twin studies allow for the investigation of genetic and environmental influences on human brain development. The generalizability of their findings depends on the developmental similarity between twins and singletons. This study aimed to evaluate the structural and functional differences in a cohort of preterm-born twins and singletons at term-equivalent age.Materials and Methods:Eighteen twins and forty-seven singletons were included and scanned at the term-equivalent age. Brain volumes from 3D T1-weighted images, quantitative metrics and structural connectivity from diffusion tensor imaging, and low-frequency brain activity and functional connectivity from resting-state functional MRI (rs-fMRI) were obtained from these neonates.Results:We found no significant volumetric differences after multiple comparison correction. The diffusivity values in the cingulum cingular part, cingulate gyrus, lateral fronto-orbital gyrus, gyrus rectus, as well as medial fronto-orbital gyrus were significantly higher in the twin group than in the singleton group. Structural connectivity analysis showed higher transitivity in the twin group compared to the singletons, indicating increased local connectivity. For rs-fMRI, the twin group showed greater fractional amplitude of low-frequency fluctuation (fALFF) values in the salience network and several fronto-temporal regions compared with the singleton group. It is worth noting that we found differences both in structural and functional measurements (MD and fALFF) in the prefrontal and cingulate cortex.Conclusion:The structural and functional differences collectively indicated that preterm-born twins may have delayed brain development compared with gestational age-matched singletons at term-equivalent age, which may be related to perinatal-neonatal problems.